Role of soap and water in the treatment of wound dehiscence compared to normal saline plus povidone-iodine: A randomized clinical trial - Najafian, Aida (J Educ Health Promot, 2015)
BACKGROUND: The incidence of cesarean section is increased. About 3–30% of the women who undergo cesarean experience surgical site infections (SSIs). Many methods, have been used to decrease the incidence of SSIs, but despite much effort, no definite efficacious method has been suggested. MATERIALS AND METHODS: In this parallel, single-blinded, randomized control trial, 56 women with post-surgical superficial wound dehiscence were divided into two groups in a 1:1 ratio. One group was irrigated with normal saline for irrigation and Firooz® baby soapand the other with normal saline for irrigation and povidone-iodine. Formation of granulation tissue was monitored in both groups. Also, the reason for surgery, length of wound dehiscence, and duration of hospitalization and wound union after were compared in both group's. RESULTS: The soap group patients were irrigated for 4.18 ± 1.96 days compared to 5.36 ± 2.83 days for the patients in povidone-iodine group (P = 0.414). The granulation tissue was formed after 3.88 ± 1.94 days in the soap group compared to 4.48 ± 2.92 days in the other group (P = 0.391), and the duration of hospitalization was 5.48 ± 2.04 days in the soap group compared to 6.3 ± 2.95 days in the other group (P = 0.423). So, no differences were observed between the two groups. CONCLUSION: It can be concluded since there is no difference between the results of two groups, irrigation with normal saline and soap is safe, easy and causes no harm or allergy compared with povidone iodine and normal saline.